PERFORMANCE OPTIMIZATION THROUGH LEARNING MANAGEMENT SYSTEM - Dedy Eko Widianto; Kiki Farida Ferine (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
This study aims to analyze the effect of Ability and Skills and Motivation on Employee Performance with Learning Management System – My Learning as an intervening variable at PT iForte Solusi Infotek West Region. The population of this study consisted of all employees at PT iForte Solusi Infotek West Region, with a total of 110 respondents selected using a saturated sampling method. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Ability and Skills have a positive and significant effect on Employee Performance, and also significantly influence the use of Learning Management System – My Learning. Motivation has a positive and significant effect on the use of the Learning Management System but does not directly affect Employee Performance. Furthermore, Learning Management System – My Learning significantly mediates the relationship between both Ability and Skills and Motivation with Employee Performance. The R² value for Employee Performance is 0.769, indicating that 76.9% of the variance in performance can be explained by the variables in the model, while 87.2% of the variance in LMS usage is explained by Ability and Skills and Motivation. This study concludes that developing employees' abilities, skills, and motivation through Learning Management System – My Learning is an effective strategy to improve employee performance. The findings provide important implications for companies in designing training programs and managing digital learning systems.